Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.4252/wjsc.v15.i5.421
|View full text |Cite
|
Sign up to set email alerts
|

Communication between bone marrow mesenchymal stem cells and multiple myeloma cells: Impact on disease progression

Daniel García-Sánchez,
Alberto González-González,
Ana Alfonso-Fernández
et al.

Abstract: Multiple myeloma (MM) is a hematological malignancy characterized by the accumulation of immunoglobulin-secreting clonal plasma cells at the bone marrow (BM). The interaction between MM cells and the BM microenvironment, and specifically BM mesenchymal stem cells (BM-MSCs), has a key role in the pathophysiology of this disease. Multiple data support the idea that BM-MSCs not only enhance the proliferation and survival of MM cells but are also involved in the resistance of MM cells to certain drugs, aiding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 133 publications
0
1
0
Order By: Relevance
“…This study found that ALP activity, type I collagen gray value, BMP-2, and Runx2 protein and mRNA expression levels in the circRNA high-level group were significantly higher than those in the circRNA low-level group, and the difference was statistically significant (P < 0.05). Similarly, studies have shown that Runx2 plays a crucial role in the osteogenic differentiation of bone marrow mesenchymal stem cells [15] . Zong et al found that the expression of circRNA was reduced in bone marrow mesenchymal stem cells of patients with osteosarcoma, and lentivirus experiments found that overexpression of circRNA can promote the osteogenic differentiation of bone marrow mesenchymal stem cells, and circRNA combined with miRNA-942-5p can regulate the expression of Runx2 and vascular endothelial growth factor (VEGF) in bone marrow mesenchymal stem cells [16] .…”
Section: Discussionmentioning
confidence: 95%
“…This study found that ALP activity, type I collagen gray value, BMP-2, and Runx2 protein and mRNA expression levels in the circRNA high-level group were significantly higher than those in the circRNA low-level group, and the difference was statistically significant (P < 0.05). Similarly, studies have shown that Runx2 plays a crucial role in the osteogenic differentiation of bone marrow mesenchymal stem cells [15] . Zong et al found that the expression of circRNA was reduced in bone marrow mesenchymal stem cells of patients with osteosarcoma, and lentivirus experiments found that overexpression of circRNA can promote the osteogenic differentiation of bone marrow mesenchymal stem cells, and circRNA combined with miRNA-942-5p can regulate the expression of Runx2 and vascular endothelial growth factor (VEGF) in bone marrow mesenchymal stem cells [16] .…”
Section: Discussionmentioning
confidence: 95%
“…In addition to cytokines/growth factors, the mTOR pathway in MM cells is modulated through various other BM-niche related factors as well. For example, cell–cell interactions with the bone marrow stromal cells (BMSCs) and osteoblasts in the BM microenvironment, mediated by RANK-RANKL binding, foster MM cell survival, growth and drug resistance via c-Src mediated mTOR signaling [ 97 , 98 ]. Moreover, cytokines such as IL-6 and binding to BMSC will also trigger overexpression of the constitutively active serine/threonine kinase Pim2, which is essential for MM survival by phosphorylating TSC2, leading to mTORC1 activation and signaling [ 99 , 100 ].…”
Section: Introductionmentioning
confidence: 99%
“…The complex interaction between mesenchymal stromal cells (MSCs) and MM cells leads to an overproduction of cytokines and growth factors that support and sustain tumor growth, progression, and therapy resistance. In this context, immune dysfunction, due to an altered T-cell repertoire with features of terminally differentiated T cells and loss of antigen-specific T-cell function, as well as ineffective antigen processing/presentation by tumor cells or dendritic cells, plays a crucial role in MM PCs survival [3,4].…”
Section: Introductionmentioning
confidence: 99%